PENGARUH KEHADIRAN DOSEN DAN PROSES PEMBELAJARAN TERHADAP PRESTASI AKADEMIK MAHASISWA PADA STMIK PROFESIONAL MAKASSAR - Rosnani (Yayasan Nusantara Hasana Berdikari, 2023)
One of the success of a university is to produce output that has good academic achievement, this can be achieved if students have good academic achievement during the learning process in college in each semester. This study aims to see the effect of lecturer attendance, learning process and student attendance on student academic achievement. This research was conducted at the College of Informatics and Computer Management (STMIK) Professional Makassar. Questionnaires will be distributed to 221 students of STMIK Professional Makasssar in odd Semester of TA.2022/ 2023, taken by random stratified sampling, the questionnaire is designed in the form of Likert scale with four options, then analyzed by multiple regression method, with significant level / α = 5 %. Analysis using SPSS 17 software. The results showed that simultaneously, academic achievement can be influenced by lecturer attendance, learning process and student attendance. The amount of influence of the 3 variables simultaneously on academic achievement is 24.5% (Value R2 = 0.245), the rest of 75.5% influenced by other factors outside the regression model. The amount of correlation between independent variables of lecturer attendance, learning process and student attendance toward student achievement is 0,495. The most influential factor on student achievement is student attendance factor because the regression coefficient of student attendance variable is bigger than the other two variables (attendance of lecturer and learning process) that is equal to 0,017.